PERFORMANCE MANAGEMENT AND EFFICIENCY OF COMMUNICATION - LIVIU NEAMTU; ADINA CLAUDIA NEAMTU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
Performance management is, in fact, that systemic coordination process through communication of actions undertaken by the firm in the context of an environment which is in a continuous movement and transformation, which anticipates changes, taking appropriate response measures, time-reacting, dynamically, flexible and quickly to these changes through appropriate strategies, which application in practice is monitored, controlled and adjusted continuously. Performance management is defined as complete and complex levels of communication on organizing through strategies, policy decisions, coordination with business plans and innovative programs and tactics along with the steps required to implement these levels in the company's activity. Performance management is the management of the company based on communication and participativ management; therefore the efficiency of communication and participativ management is the foundation of performance management, it outlines the priorities, thus becoming the basic factor in the development of management programs and in the course of their ongoing. Consequently, for running relevant and profitable a business, a company needs performance management areas well-delineated, with specific tasks, that can transform customer or generally the society needs into profitable business opportunities.